Therapeutic and diagnostic difficulties concerning verrucae of the nail apparatus - a description of selected cases - Andrzej K. Jaworek; Judyta Maciejowska-Podosek; Karolina Englert; Magdalena Sarek; Anna Wojas-Pelc (Termedia Publishing House, 2020)
Verruca is a general term for lesions that are clinical manifestations of an infection with human papillomavirus (HPV). A particularly difficult (both diagnostically and therapeutically) site of verrucae is the nail apparatus within which anatomical conditions significantly hinder successful treatment of these common skin infections. The aim of the article is to present a series of three cases of patients with verrucae within the nail apparatus, including one case with a secondary involvement of the vermillion boarder due to biting and chewing the nail apparatus area. Diagnostics and treatment of nail apparatus verrucae constitute a special challenge in everyday dermatological practice due to its unique and hard-to-reach anatomical site as well as the risk for secondary HPV infections and development of nail unit squamous cell carcinoma.